If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -5 = 14x + -41 Reorder the terms: -5 + 5x = 14x + -41 Reorder the terms: -5 + 5x = -41 + 14x Solving -5 + 5x = -41 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -5 + 5x + -14x = -41 + 14x + -14x Combine like terms: 5x + -14x = -9x -5 + -9x = -41 + 14x + -14x Combine like terms: 14x + -14x = 0 -5 + -9x = -41 + 0 -5 + -9x = -41 Add '5' to each side of the equation. -5 + 5 + -9x = -41 + 5 Combine like terms: -5 + 5 = 0 0 + -9x = -41 + 5 -9x = -41 + 5 Combine like terms: -41 + 5 = -36 -9x = -36 Divide each side by '-9'. x = 4 Simplifying x = 4
| .333k-4=9 | | a^2=0 | | .33k-4=9 | | 4x^2-22x+10=0 | | 5-7x=29-28x | | x^2=-3 | | 6x=-4 | | 3y+24y+45=0 | | 4n^2-20n+24=0 | | 18b^2+24b-10=0 | | 2a^2-16a+32=0 | | 2x+4=x-5 | | 7x+7-x+7-2x-8=42 | | 3n+5=2n+7 | | 3[2x-1]=-10[x-5] | | 13-8x=22-15x | | 3x^4-5x^2-12=0 | | 3x^2+10x+17=0 | | -5x-6x=5-8x | | 8m+3n-6m+11n= | | -3x+6(3x-3)=1-4x | | -3x+6(3x-3)=1 | | 278-5x=40x+18 | | 14-7x=54-21x | | 3x+12=-38x-7x | | 3(x-4)-(5-2x)=4x-7 | | 110x=10y | | 6(2y-5)=(4y+3)9 | | 10111x=1241y | | 15a+3=-57 | | x^2-4x-7=0 | | y=-11x-3 |